ANALYSIS OF UNDERSTANDING BASIC CONCEPT MATHEMATICS - Abdul Kadir; Cut Zulisna Fonda (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2021)
The study aims to analyze the understanding of students' basic mathematical concerts. The Basic concepts mathematics studied include subtraction, multiplication and division operations.This study uses a descriptive qualitative research method.The sample of this research is electrical engineering universitas malikussaleh new students.Data collection techniques in this study by test.Data analysis techniques in this study used descriptive statistics.The results showed indicate that new students still do not understand the concept of operation multiplication, both ordinary multiplication and multiplication involving negative numbers.For subtraction operation involving negative numbers, new students already understand the concept of subtraction.For the concept of division with zero obtained 62.3% who already understand the concept of division